Integration of Christian Ethical Values in the Indonesian Education System Based on the Study of the Law of Love - Daulat Marulitua Tambunan; Lenny Helena Sacharissa Chendralisan; Jusen Jusen; William Wiguna (MASI Mandiri Edukasi, 2026)
This study examines the dynamic interaction between Christian ethical values and the education system in Indonesia, the country with the fourth largest Christian population in the world, which is based on the ideology of Pancasila. The background to this study is the tension and harmony in the process of integrating ethical values derived from the teachings of Jesus Christ and the Bible as the highest authority into the national education system. This study aims to: (1) analyze Christian ethical values as the philosophical foundation of education; (2) examine the form and implications of the codification of the law of love in the context of education; and (3) formulate a conceptual model that explains the relationship between Christian ethics and the Indonesian education system. The approach used is qualitative with a multiple case study design, combining normative analysis, document studies, in-depth interviews with educational actors, and observations at three representative locations, including Rahmat Emmanuel Theological College. The main findings show that the integration of Christian ethical values is not intended as a Christianization of the education system, but rather as the instillation of moral values in line with the National Education System Law No. 20 of 2003. The national education system functions accommodatively, enabling the realization of value pluralism through functional codification. Theoretically, this research contributes by formulating a